Second-generation immigrants: Citizenship and transnationalism / Inmigrantes de segunda generación: ciudadanía y transnacionalismo - Wihtol de Wenden, Catherine (Araucaria, 2014)
This article deals with a socio-historical approach of “second-generation immigrants” in France, a country which has a long story of immigration, but which has refused this historical past for a long time. Two tools of comprehension are used: On one hand, intersectionnality of belongings, which puts all elements of them in competition (Arab, Muslim, French, segregated in poor districts); work, however, has ceased to be an identity of recognition. On the other, a transnationality that cuts through the frontiers and the walls by identity and plural relations. After an historical perspective of the phenomenon “secondgeneration immigrants” in France, the article examines the various factors of identification that are competing together.